(untitled) (Journal of Humanitarian and Applied Sciences, 2023)
The chapter on addition is one of the broadest chapters of Arabic, and its issues have received the attention of grammarians, ancient and modern, and the visual and Kufic grammarians differed on the issue of adding the adjective to the descriptive. Each of the two Madhab sought to provide evidence and arguments that support his statement in this matter. In this study, we stand on this issue, and to include its evidence and discuss it